2017
DOI: 10.1016/j.jjcc.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Variation in effectiveness of a cardiac auscultation training class with a cardiology patient simulator among heart sounds and murmurs

Abstract: Medical students may be less likely to correctly identify S2/S3/S4 as compared with heart murmurs in a situation close to clinical setting even immediately after training. We may have to consider such a characteristic of students when we provide them with cardiac auscultation training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…To the best of our knowledge, there has been no other study in which real-time remote auscultation and classical auscultation were directly compared. In terms of the accuracy of classical auscultation using the simulator, our results, which showed variable accuracy depending on the type of sounds, were consistent with previous studies [ 10 , 22 ]. In both previous studies, the total accuracies varied from 62% to 89.7%, which may have depended on the difficulty of tests.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, there has been no other study in which real-time remote auscultation and classical auscultation were directly compared. In terms of the accuracy of classical auscultation using the simulator, our results, which showed variable accuracy depending on the type of sounds, were consistent with previous studies [ 10 , 22 ]. In both previous studies, the total accuracies varied from 62% to 89.7%, which may have depended on the difficulty of tests.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies. 2,20 This is likely to reflect relatively easier auscultatory comprehension about systolic murmur and tougher auscultatory identification about diastolic murmur. Interpretation of a rare sound such as pericardial friction rub is difficult, but it can be learnt easily since it is a specific sound which can be differentiated from other sounds.…”
Section: Pre-and Post-testmentioning
confidence: 99%
“…We have provided fourth-year medical students at Tohoku University School of Medicine with a 3-h cardiac auscultation class using a cardiology patient simulator since 2010. From 2010 to 2012, a total of 324 students, divided into groups of 6-8 students, participated in the class [ 15 ]. Using two different types of auscultation test in the class, we demonstrated that the medical students were less likely to correctly identify S2/S3/S4 as compared with heart murmurs in a situation close to clinical setting.…”
Section: Introductionmentioning
confidence: 99%